Prognostic impact of nodal status and therapeutic implications - Ott, Katja; Blank, Susanne; Peters, Leila; Schmidt, Thomas (Translational gastroenterology and hepatology, 2017)
The prognostic impact of lymph node (LN) metastases in gastric cancer is generally accepted. In primarily resected patients the pN-category and LN ratio are independent prognostic factors. Number of involved LNs, number of resected LNs, lymphangiosis and micrometastases also influence the prognosis significantly. To guarantee a proper D2 lymphadenectomy (LAD) at least 25 LNs according to the German S3 guidelines for the treatment of gastric cancer should be removed. Also in neoadjuvantly treated patients the ypN-category and LN ratio play an important prognostic role, despite the fact that UICC staging system was development based only on primarily resected patients. The role of response of LNs in neoadjuvantly treated patients is still unclear and needs further investigation. It seems to be less important than the response of the primary tumor. Limited data exists, suggesting that preoperative treatment might reduce the number of LNs involved and improve ypN-category. Due to further development in gastric cancer like laparoscopic resection and effective perioperative treatment in locally advanced tumor the role and the prognostic impact of LAD is again in the focus of discussion.
Gesehen am 05.04.2018